How STEAM is a Chemistry textbook for class XI of a public high school in Surakarta - Durrotunnisa Fathia Rahma; Sri Retno Dwi Ariani; Mohammad Masykuri (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to analyze the content of the STEAM aspect in the chemistry textbook for class XI. The research method used is descriptive qualitative. Data collection in this study used content analysis techniques. The sampling technique used is purposive sampling. The data sources used are the Chemistry Book for SMA/MA Class XI Specialization in Mathematics and Natural Sciences published by Erlangga in 2016 as book A, Experiment-based Chemistry Student Book published by Tiga Serangkai in 2014 as book B, and Chemistry Student Books for SMA/MA Class XI publisher Intan Pariwara in 2016 as book C. Basic Competencies analyzed in the three books, namely Hydrocarbon Compounds and Petroleum represent KD which are conceptual-theoretical, Reaction Rate represents KD which is mathematical, and Chemical Equilibrium represents KD which is abstract-complex. The results showed that books A, B, and C already contained all aspects of STEAM in various basic competencies. The contents of STEAM aspects in book A are 80 statements, book B are 85 statements, and book C are 121 statements. In Books A and C, the aspects of STEAM that are mostly covered are the mathematical aspects, while the aspects that are mostly published in Book B are the science aspects. The aspects of STEAM that are least contained in books A and B are the artistic aspects, while in book C are the technical and artistic aspects. Thus, in books A, B, and C, the artistic aspect has a low amount of load. Research on the content of STEAM and HOTS aspects needs to be carried out in more depth with a different approach regarding the integration of STEAM and HOTS aspects, especially in textbooks and other learning resources.